Development and characterization of cotton and cotton fabric reinforced geopolymer composites - Alomayri, Thamer Salman (Curtin University, 2015)
Sustainable geopolymer composites reinforced with natural cotton fibres have been developed and their mechanical and durability properties are evaluated in this research. Results showed that the mechanical properties (flexural strength, flexural modulus, fracture toughness, compressive strength, impact strength and hardness) of woven cotton fabric-reinforced geopolymer composites were superior to those of geopolymer composites with short cotton fibres. Exposure to water and elevated temperatures (200 to 1000°C) severely reduced the mechanical properties of the composites.